Analisis Pemanfaatan Internet dalam Usaha Ekonomi Kreatif Kuliner Bustaman di Masa Pandemi Covid-19 - Wardha, Fira Fahmi Raihanul; Artiningsih, Artiningsih (Teknik PWK (Perencanaan Wilayah Kota), 2023)
The creative economy is an economic concept that utilizes creative assets in the form of creativity and and also as the use of technology in the process. Culinary is one of the sub-sectors in the creative economy. The culinary business has been the economic basis of the people of Kampung Bustaman, Semarang City for generations. The emergence of the corona virus pandemic and the Covid-19 pandemic put forth to efforts to handle and prevent the spread through Large-Scale Social Restrictions (PSBB), which on the other hand also has an impact on the limited culinary business activities. That has resulted in low levels of mobility and consumption, also as a shift in the buying and selling system from offline to online. The existence of a pandemic can encourage Bustaman culinary business actors to try opportunities and advantages in the culinary business through the use of digital technology or the internet. The aim of this research is to analyze the use of the internet in Bustaman's culinary creative economy during the Covid-19 Pandemic. Using crosstab quantitative descriptive research method, with Bustaman culinary business actors as the sample. This study shows that there are 83,3% of business actors who use the internet in their business. The form of utilization carried out is to promote and market culinary online through various platforms and available applications such as messaging applications, social media and food delivery.